Fading Cultural Identity among High School Students: An Analysis of Low "Adiluhung" Cultural Literacy in Indonesia - Hifdiyah, Shinta Nuriyatil (Fast in Humanities, 2026)
This study aims to examine how low levels of adiluhung cultural literacy and ineffective cultural mediation contribute to the fading of cultural identity among Indonesian high school students. Against the backdrop of increasing globalization, adiluhung culture representing noble national values continues to be formally present in educational settings, yet its role in shaping students’ identity remains questionable. Employing a qualitative descriptive-analytical design, the study involved purposively selected senior high school students. Data were collected through in-depth interviews, open-ended questionnaires, and document analysis, and were analyzed using an interactive model supported by technique and source triangulation. The findings indicate that students’ adiluhung cultural literacy is largely fragile, characterized by surface-level recognition of cultural symbols without interpretive understanding or value internalization. Cultural exposure in schools tends to be limited, episodic, and predominantly formalistic, offering minimal opportunities for sustained or experiential engagement. Consequently, students demonstrate identity ambivalence: while cognitively acknowledging the importance of national culture, they orient their self-expression toward global cultural forms perceived as more relevant to contemporary life. The discussion shows that this condition reflects a failure of cultural mediation, in which cultural knowledge exists but does not function as a meaningful resource for cultural identity formation. This study concludes that the weakening of students’ cultural identity is driven less by cultural loss than by inadequate mediation between cultural exposure, cultural literacy, and lived experience. Strengthening cultural identity therefore requires interpretive and experiential cultural education that enables adiluhung culture to operate as a living source of meaning within globalized educational contexts.